Optimization of Starch Saccharification Process and Structural Characterization of Starch Using Low Transglycosidation Activity Glucoamylase GluM3 - Haiyue FAN; Zhao YU; Zhengjie ZHANG; Ming LI; Yingguo BAI; Feng YU; Zhongyuan LI (Shipin gongye ke-ji)
This paper discussed the optimization of the corn starch saccharification process using the glucoamylase GluM3, and explored its impact on the structure of starch granules to further promote the industrial application of GluM3 in starch sugar production. The study first determined the optimal saccharification process for low transglycosylation activity glucoamylase GluM3 through single-factor experiments and response surface experiments. Structural characterization of starch granules was conducted using methods such as scanning electron microscopy, X-ray diffraction, and infrared spectroscopy. The results showed that the optimal saccharification conditions were a liquefaction DE value of 16%, temperature at 66 ℃, pH at 3.7, time at 3 h, enzyme dosage at 450 U/g with pullulanase dosage at 1.25 U/g. After optimization, the glucose content (DX value) in corn starch saccharification liquid reached 92.68%. After saccharification reaction, corn starch changed from smooth intact particles to fragmented debris state. There was a certain degree of damage to internal crystalline structure during saccharification. A decrease in short-range order degree after saccharification reaction was observed. Furthermore, various maltodextrins were produced after corn starch enzymatic hydrolysis reaction while maltodextrins were further converted into glucose by GluM3 with a proportion as high as 99.34%. This study establishes the optimal saccharification process for low transglycosylation activity GluM3 on corn starch and investigates changes in microstructure and physical properties during the saccharification process, providing theoretical basis for subsequent industrial applications of GluM3.